The regulation of TIM-3 transcription in T cells involves c-Jun binding but not CpG methylation at the TIM-3 promoter. (July 2016) - Yun, Su Jin; Jun, Ka-Jung; Komori, Kuniharu; Lee, Mi Jin; Kwon, Myung-Hee; Chwae, Yong-Joon; Kim, Kyongmin; Shin, Ho-Joon; Park, Sun
Highlights: CpG methylation of the TIM-3 promoter did not change during T cell activation. Histone H3 methylation of the TIM-3 promoter did not change during T cell activation. AP-1 is involved in TIM-3 transcription in T cells. c-Jun protein interacts with the TIM-3 minimal promoter. Abstract: Tim-3 is an immunomodulatory protein that is expressed constitutively on monocytes but is induced in activated T cells. The mechanisms involved in the regulation of TIM-3 transcription are poorly understood. In the present study, we investigated whether methylation of the TIM-3 promoter is involved in regulatingTIM-3 transcription in T cells, and identified a transcription factor that regulates TIM-3 transcription by associating with the TIM-3 minimal promoter region. Pyrosequencing of the TIM-3 promoter up to −1440 bp revealed 11 hypermethylated CpG sites and 4 hypomethylated CpG sites in human CD4 + T cells as well as in CD11b + cells. Dimethylation of histone H3 lysine 4 (H3K4), a mark of transcriptional activation, was predominantly found in the proximal TIM-3 promoter −954 to −34 bp region, whereas trimethylation of H3K9 and H3K27, which are markers of transcriptional suppression, were mostly observed in the distal promoter −1549 to −1048 bp region in human CD4 + T cells and CD11b + cells. However, no change in the methylation status of CpG sites and the histone H3 in the TIM-3 promoter was found during induction of TIM-3 transcription in T cells. Finally, AP-1 involvement in TIM-3 transcription was shown in relation with the TIM-3 minimal promoter −146 to +144 bp region. The present study defines the minimal TIM-3 promoter region and demonstrates its interaction with c-Jun during TIM-3 transcription in CD4 + T cells.